MENGENAL METODE KONTRASEPSI YANG TEPAT UNTUK KELUARGA BERENCANA DI DESA PODOSARI KECAMATAN PRINGSEWU KABUPATEN PRINGSEWU LAMPUNG - Setia Anggraini, Sesi (Jurnal Pengabdian Kepada Masyarakat Ungu( ABDI KE UNGU), 2024)
Background: the holding of this "Contraceptive Methods" counseling is that the fact that there are still many people who do not know the whole about what is family planning and contraceptive methods. Objectives: This activity was carried out to increase the knowledge and interest of participants regarding family planning programs and introduce hormonal, non-hormonal, steady methods, and also natural contraceptives as appropriate contraceptives for use by women of childbearing age. The material presented is the definition of family planning, contraceptive methods such as hormonal, non-hormonal, steady and natural contraceptive methods. After the delivery of the material, a question and answer session was continued where all participants were given the opportunity to ask questions related to the material provided and participants were asked questions and shared their experiences in using contraceptives. Results: what was obtained after the implementation of this activity was that the participants' knowledge and understanding increased about the family planning program and knew various contraceptive methods. Therefore, through this activity it is hoped that it can increase the knowledge of the participants about contraceptive methods so that it can increase the use of contraceptives in the area, besides that it is hoped that the participants will have the ability to choose contraceptive methods that are suitable and in accordance with their current conditions.